Does adding an aortic root replacement or sinus repair during arch repair increase postoperative mortality? Evidence from the Canadian Thoracic Aortic Collaborative. (26th March 2021) - Hage, Fadi; Hage, Ali; Dagenais, Francois; Cartier, Andreanne; Ouzounian, Maral; Chung, Jennifer; El-Hamamsy, Ismail; Chauvette, Vincent; Peterson, Mark D; Lachapelle, Kevin; Ridwan, Khalid; Boodhwani, Munir; et al.
Abstract:  : OBJECTIVES: The aim of this study was to examine the effect of the addition of an aortic root replacement or sinus repair on mortality and morbidity during aortic arch repair. METHODS: A total of 2472 patients underwent proximal or total aortic arch repair with hypothermic circulatory arrest between 2002 and 2018 at 12 centres. Multivariable logistic regressions (MV) and propensity score (PS) with inverse probability of treatment weighting (IPTW) analyses were performed. RESULTS: A total of 1099 (44.5%) patients had additional aortic root replacement ( n  = 934) or sinus repair ( n  = 165). Those with aortic root interventions were younger (61 ± 13 vs 64 ± 13 years, P  < 0.001) and had less females (23% vs 35%, P  < 0.001), less dissection (31% vs 36%, P  = 0.004), less urgent cases (35% vs 39%, P  = 0.047), more connective tissue disease (7% vs 3%, P  < 0.001) and less total arch replacements (14% vs 22%, P  < 0.001). On adjusted analyses, the addition of aortic root procedure was associated with increased mortality [MV: odds ratio (OR) 1.41, 95% confidence interval (CI) 1.03–1.92; PS-IPTW: risk increased by 3.7%, 95% CI 1.2–6.3%, P  = 0.004]. Reoperation for bleeding was also increased with the addition of aortic root intervention (MV: OR 1.48, 95% 1.10–1.99; PS-IPTW: risk increased by 3.2%, 95% CI 0.8–5.6%, P  = 0.009). The risks of stroke and dialysis-dependent renal failure were similar. When looking only at non-elective cases, the increased risk of mortality was more pronounced (MV: OR 1.60, 95% CI 1.11–2.32, P  = 0.013; PS-IPTW: risk increased by 6.8%, 95 CI 1.7–11.8%, P  = 0.008, and a number need to harm of 15 patients to cause 1 additional death). CONCLUSIONS: The addition of aortic root replacement or sinus repair during proximal or total aortic arch repair seems to increase postoperative mortality only in non-elective cases.